Analisis Formulasi Kebijakan Program Bangun Jalan Desa Sejahtera (Bang Andra) dalam Pembangunan Infrastruktur Jalan Desa di Provinsi Banten - Nur’aini N; Laeli Nur Khanifah; Salsa Elsa Ulandari; Naura Allevia Tamsil; Puspa Indah Rahayu (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the policy formulation of the Prosperous Village Road Building Program (Bang Andra) in the development of village road infrastructure in Banten Province using William N. Dunn's theory. This study uses a descriptive qualitative method with a case study approach. Data were collected through interviews, documentation, and observation, then analyzed using the Miles and Huberman model. The results of the study indicate that the policy formulation of the Bang Andra Program goes through four stages, namely problem identification, agenda development, alternative development, and policy determination. This program was born as a response to the low quality of village roads that hamper community mobility and economic activities. This issue then became a priority for the local government and was stipulated through Banten Governor Regulation Number 17 of 2025. In 2025, the Bang Andra Program succeeded in building 62 village infrastructures consisting of 61 road sections and 1 bridge with a length of 67.87 kilometers with a budget of IDR 184 billion. This study concludes that the policy formulation of the Bang Andra Program reflects the local government's efforts to improve connectivity and equitable distribution of village development in Banten Province.